Common variants of the BRCA1 wild-type allele modify the risk of breast cancer in BRCA1 mutation carriers - Cox, David G.; Hamann, Ute; Sutter, Christian (Human molecular genetics, 2011)
Mutations in the BRCA1 gene substantially increase a woman's lifetime risk of breast cancer. However, there is great variation in this increase in risk with several genetic and non-genetic modifiers identified. The BRCA1 protein plays a central role in DNA repair, a mechanism that is particularly instrumental in safeguarding cells against tumorigenesis. We hypothesized that polymorphisms that alter the expression and/or function of BRCA1 carried on the wild-type (non-mutated) copy of the BRCA1 gene would modify the risk of breast cancer in carriers of BRCA1 mutations. A total of 9874 BRCA1 mutation carriers were available in the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA) for haplotype analyses of BRCA1. Women carrying the rare allele of single nucleotide polymorphism rs16942 on the wild-type copy of BRCA1 were at decreased risk of breast cancer (hazard ratio 0.86, 95% confidence interval 0.77-0.95, P = 0.003). Promoter in vitro assays of the major BRCA1 haplotypes showed that common polymorphisms in the regulatory region alter its activity and that this effect may be attributed to the differential binding affinity of nuclear proteins. In conclusion, variants on the wild-type copy of BRCA1 modify risk of breast cancer among carriers of BRCA1 mutations, possibly by altering the efficiency of BRCA1 transcription.